Corona crisis plagues, pandemics, and the coming apocalypse - Hitchcock, Mark 1959- (W Publishing Group, 2020)
"The world has not seen such a pandemic in generations. And as the world fights COVID-19, is God trying to send a message? Pastor and Dallas Theological Seminary professor Mark Hitchcock shares how the current coronavirus outbreak is related to end-time prophecies"-- Source other than the Library of Congress.